Structure and Classification of Unified Energy Agents as a base for the systematic development of Future - Derksen, Christian; Linnenberg, Tobias; Unland, Rainer; Fay, Alexander (EAAI - Engineering Applications of Artificial Intelligence, 2015)
The ongoing conversion of our energy supply encounters a great interest of many different market players that were originally located in different industries. As a consequence, a vast amount of proprietary solutions for “smart” energy applications is flooding the market. This tends to be rather a problem than part of the solution for the systematic development of future energy grids. Here, the absence of necessary unifications and standards blocks further developments that would enable the creation of novel, market-driven and hybrid control solutions for various types of technical systems. To overcome these problems, we present in this article our notion and the definition of a unified autonomous software entity that we call Energy Agent. Based on the energy conservation law and a generalized energy option model, we claim that our Energy Agent approach has the capabilities to enable cross domain interactions between different types of energy systems and networks. Further we will outline a systematic development process for Energy Agents that considers implementation, simulation, test-bed application and a real on-site usage. By taking into account these development stages, we expect to concurrently develop a novel laboratory that enables to competitively test and validate new and hybrid control solutions before they are applied in real systems.